2000
DOI: 10.1152/ajpheart.2000.279.2.h808
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic β2-adrenoceptors mediate nicotine-induced NOergic neurogenic dilation in porcine basilar arteries

Abstract: We previously reported that nicotine-induced nitric oxide (NO)-mediated cerebral neurogenic vasodilation was dependent on intact sympathetic innervation. We hypothesized that nicotine acted on sympathetic nerve terminals to release norepinephrine (NE), which then acted on adrenoceptors located on the neighboring nitric oxidergic (NOergic) nerve terminals to release NO, resulting in vasodilation. The adrenoceptor subtype in mediating nicotine-induced vasodilation in isolated porcine basilar arterial rings denud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 24 publications
14
63
0
Order By: Relevance
“…The relaxation elicited by repeated TNS at 2, 4, and 8 Hz, like other reports in the porcine basilar arteries (Zhang et al, 1998;Lee et al, 2000), was reproducible on repeated application. In basilar arteries (without endothelial cells) in the presence of active muscle tone induced by U-46619 (0.3 mmol/L), relaxation induced 2, 4, and 8 Hz TNS was significantly inhibited by all three ChEIs at each concentration tested; physostigmine (3 to 30 mmol/L), neostigmine (3 to 30 mmol/L) and galantamine (10 to 100 mmol/L) ( Figures 1A and 1B, 2D-2F, 3D-3F and 4D-4F).…”
Section: Cholinesterase Inhibitors Inhibited Transmural Nerve Stimulasupporting
confidence: 85%
“…The relaxation elicited by repeated TNS at 2, 4, and 8 Hz, like other reports in the porcine basilar arteries (Zhang et al, 1998;Lee et al, 2000), was reproducible on repeated application. In basilar arteries (without endothelial cells) in the presence of active muscle tone induced by U-46619 (0.3 mmol/L), relaxation induced 2, 4, and 8 Hz TNS was significantly inhibited by all three ChEIs at each concentration tested; physostigmine (3 to 30 mmol/L), neostigmine (3 to 30 mmol/L) and galantamine (10 to 100 mmol/L) ( Figures 1A and 1B, 2D-2F, 3D-3F and 4D-4F).…”
Section: Cholinesterase Inhibitors Inhibited Transmural Nerve Stimulasupporting
confidence: 85%
“…In addition, other mechanisms may also modulate the function of adrenergic nerves, and these complicating factors must also be addressed. For example, our studies and others have shown that the SCG (Dun et al, 1995;Wu et al, 1997) and the cerebral vasculature contain adrenergic and neuronal nitric oxide (nNOS) containing nerves; NO released from nNOS neurons facilitates stimulation-evoked NA release in both blood vessels and the CNS (Montague et al, 1994;Yamamoto et al, 1997;Zhang et al, 1998;Lee et al, 2000;Mbaku et al, 2000Mbaku et al, , 2003. Facilitated function of adrenergic nerves via nNOS nerves may occur through enhancement of Ca 2+ influx and/or Ca 2+ release from internal stores.…”
Section: Aging Alters Function Of Adrenergic Neurons Via Multiple Mecmentioning
confidence: 78%
“…The relative significance of a 2-adrenoceptors located on adrenergic sympathetic nerve terminals and nitrergic nerve terminals in mediating nicotine-induced NO-mediated relaxation remains to be determined. The presynaptic b2-adrenoceptors on nitrergic nerve terminals, however, appear to be predominant in cerebral perivascular nerves, since nicotineinduced NE-mediated nitrergic vasodilation in the absence of yohimbine was demonstrated (34).…”
Section: Nicotine-induced No-mediated Cerebral Neurogenic Vasodilatiomentioning
confidence: 97%
“…Nicotine-induced neurogenic vasodilation is blocked by , , , ,2-but not , , , , 1-adrenoceptor antagonists Clarification of adrenoceptors mediating nicotineinduced relaxation of isolated large cerebral arteries has provided evidence that NE is the mediator in nicotineinduced NO-mediated neurogenic vasodilation (34). In the presence of active muscle tone induced by U46619 (0.3 µM) in isolated porcine basilar arteries without endothelial cells, nicotine (100 mM)-induced relaxation was significantly inhibited by propranolol (0.1 -10 mM) in a concentration-dependent manner (Fig.…”
Section: Nicotine-induced No-mediated Cerebral Neurogenic Vasodilatiomentioning
confidence: 99%